Developing Dynamic Digital Image Correlation Technique to Monitor Structural Damage of Old Buildings under External Excitation - Ming-Hsiang Shih; Wen-Pei Sung (Shock and Vibration)
The capacity of buildings to resist external excitation is an important factor to consider for the structural design of buildings. When subject to external excitation, a building may suffer a certain degree of damages, and its residual capacity to resist external excitation cannot be evaluated. In this research, dynamic digital image correlation method combined with parameter evaluation available in system identification is used to evaluate the structural capacity to resist external excitation. The results reveal possible building latent safety problems so that timely structural reinforcement or dismantling of the building can be initiated to alleviate further damages. The results of experiments using the proposed method conform to the results obtained using the conventional method, but this method is more convenient and rapid than the latter in the subsequent procedure of data processing. If only the frequency change is used, the damages suffered by the building can be detected, but the damage location is not revealed. The interstory drift mode shape (IDMS) based on the characteristic of story drift has higher sensitivity than the approximate story damage index (ADSI) method based on modal frequency and vibration type; however, both indices can be used to determine the degree and location of building damages.